Intersepsi Pesawat Jet Tempur Rusia Terhadap Pesawat Mata-mata Amerika Serikat di Wilayah Udara Laut Medeterania Berdasarkan Hukum Internasional - Ekayanti, Rafita; Nugroho, Arinto; Puspoayu, Elisabeth Septin (NOVUM : JURNAL HUKUM)
Abstract Russian fighter jets with aircraft code SU-35 flew in the international airspace of the Mediterranean Sea region on June 4, 2019. At the same time, the American spy plane, code number P-8A Poseidon, also flew in the same area was subject to interception which was carried out unsafe and incompatible with the interception procedure for aircraft in international airspace by Russian warplanes. International law regulates everything that can endanger the safety and security of an aircraft in international airspace as regulated in the provisions of Appendix 3 regarding aircraft maneuvers and interception. The purpose of this study is to analyze the form of responsibility and sanctions that can be given regarding the interception of Russian fighter jets against US spy planes in the international airspace of the Mediterranean Sea. This research is a normative legal research using a statutory and conceptual approach. The legal materials for this research consist of primary and secondary legal materials. State responsibility that can be applied in this case is in the form of satisfaction because there is no physical loss, only in the form of turbulence that does not cause casualties. Meanwhile, the sanctions that can be applied are fines by the United Nations Security Council and resolutions issued by the General Assembly of the United Nations in the form of recommendations related to air violations. Keywords: Interception, International Law, State Responsibility, Sanctions